Dig your well before you're thirsty the only networking book you'll ever need - Mackay, Harvey (New York Currency/Doubleday, 1997)
Harvey Mackay, who taught millions of Americans how to "swim with the sharks without getting eaten alive" now dives deep into the art of which he's grandmaster: networking. Dig Your Well Before You're Thirsty contains Harvey's gold-chip advice, accumulated over a lifetime of business success, on how to build and maintain the network you need. Harvey guarantees you'll never be more than a phone call away from a person in the position to help you get what you want.
whether it's the job opportunity of a lifetime or a lifetime partner, the sales prospect of your dreams or the career advice you've only dreamed of. Harvey shows you how to create a network of trusted, valuable contacts that is worth its weight in platinum. Harvey show you step by step how to get to know the people you need to know; how to keep relationships up-to-date and alive; how to ask for what you need when you need it; how to sparkle in the information age and on.
the Internet; and how to unlock any door ... anywhere ... at any time. Learn from Harvey's own energizing examples and those he gleaned from world-class networkers like Muhammad Ali, Lou Holtz, Erma Bombeck, Larry King, and Pat O'Brien.
"A Currency book."
Includes index.
Keywords: Business networks; Social networks